2017
DOI: 10.2196/mhealth.7014
|View full text |Cite
|
Sign up to set email alerts
|

Consent Processes for Mobile App Mediated Research: Systematic Review

Abstract: BackgroundSince the launch of ResearchKit on the iOS platform in March 2015 and ResearchStack on the Android platform in June 2016, many academic and commercial institutions around the world have adapted these frameworks to develop mobile app-based research studies. These studies cover a wide variety of subject areas including melanoma, cardiomyopathy, and autism. Additionally, these app-based studies target a variety of participant populations, including children and pregnant women.ObjectiveThe aim of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 9 publications
(12 reference statements)
0
33
0
Order By: Relevance
“…A total of 32 references has been included in this review. (Figure 1) Of these, 18 references were journal articles, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] seven reviews, [27][28][29][30][31][32][33] three systematic reviews, [34][35][36] two survey results from Australia 37 and the USA, 38 one study report from Germany 6 and one qualitative study from Australia. 39 For further discourse, the principles of biomedical ethics defined by Beauchamp and Childress function as ethical endpoints.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 32 references has been included in this review. (Figure 1) Of these, 18 references were journal articles, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] seven reviews, [27][28][29][30][31][32][33] three systematic reviews, [34][35][36] two survey results from Australia 37 and the USA, 38 one study report from Germany 6 and one qualitative study from Australia. 39 For further discourse, the principles of biomedical ethics defined by Beauchamp and Childress function as ethical endpoints.…”
Section: Resultsmentioning
confidence: 99%
“…25 In addition, several publications have highlighted the use of health applications in research and related ethical challenges. 16,31,32,38 Five publications deal with ethical concerns regarding the regulation and approval of health and medical apps. 6,11,18,33,34 Only one publication addresses developers of health and medical apps and emphasises ethical principles that should be considered in the development phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other efforts have explored interface designs intended to slow users down in the hopes of increasing comprehension [70], and the use of learning theory to design consent content [71]. A review of research on consent processes for research mediated by mobile apps found a range of practices, including some not found in traditional consent, such as assessments of consent understanding and the use of finger-drawn singatures [72]. The broad range of delivery methods, study designs, and assessments used in these studies suggests a need for further work to better understand which approaches might work best in which contexts.…”
Section: Consent Trust and Participant Engagementmentioning
confidence: 99%